2011
DOI: 10.1002/mus.22002
|View full text |Cite
|
Sign up to set email alerts
|

Topical naphazoline in the treatment of myasthenic blepharoptosis

Abstract: Topical naphazoline was found to be an effective supplementary symptomatic treatment for myasthenic blepharoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Naphazoline, a primary α2-agonist, selectively increases the tone of Muller muscles without mydriasis and successfully reduces myasthenic ptosis [20]. Although rapid effects of topical naphazoline without significant adverse effects were observed in 70% of the MG patients in a previous study, their responses were variable and temporary [20]. In cases of long-standing and irreversible ptosis, surgery for ptosis may be considered [21].…”
Section: Discussionmentioning
confidence: 99%
“…Naphazoline, a primary α2-agonist, selectively increases the tone of Muller muscles without mydriasis and successfully reduces myasthenic ptosis [20]. Although rapid effects of topical naphazoline without significant adverse effects were observed in 70% of the MG patients in a previous study, their responses were variable and temporary [20]. In cases of long-standing and irreversible ptosis, surgery for ptosis may be considered [21].…”
Section: Discussionmentioning
confidence: 99%
“…73 One recent multicenter joint study reported 71.7% usefulness of naphazoline eye drops against eyelid ptosis in 60 MG patients. 73 If eyelid ptosis does not respond to treatment and persists, surgery might be able to repair eyelid function and appearance. There are few studies on the long-term course after surgery or with large sample sizes, but surgery should yield good therapeutic effects as long as the case selection, timing, procedure and surgeon are all appropriate.…”
Section: Recommendationsmentioning
confidence: 99%
“…Eye drops of the α 2 ‐adrenoceptor stimulant, naphazoline, strengthen contraction of Müller's muscle, thereby improving some muscle disorders and eyelid ptosis resulting from partial Horner syndrome . One recent multicenter joint study reported 71.7% usefulness of naphazoline eye drops against eyelid ptosis in 60 MG patients …”
Section: Treatment Strategies For Ocular Mgmentioning
confidence: 99%
“…Moreover, while corticosteroids are very effective in the short term, long-term adverse effects occur in up to 38% of cases 11,12. Thus, neurologists often struggle to treat patients with medically refractory longstanding blepharoptosis 13–15…”
Section: Introductionmentioning
confidence: 99%